Development of Cognitive Competence of Computer Science Teachers (Texas Journal of Multidisciplinary Studies, 2022)
Human society is unthinkable outside of communication. Communication is a necessary condition for the existence of people, without which it is impossible to fully form not only individual mental functions, processes and properties of a person, but also the personality as a whole. The reality and necessity of communication is determined by joint activity: in order to live, people are forced tointeract. Always an active person communicates, whose activities intersect with theactivities of other people. Communication allows you to organize social activities and enrich it with new connections and relationships between people.